Allowing Natural Sedimentation in the Nieuwe Waterweg to Reduce Salinity Intrusion and the Effects of Sea Level Rise - Kleinhans, Maarten; Baltussen, Silke; Nota, Eise; Cox, Jana; Meijer, Han; Hugtenburg, Jasper (Blue Papers, 2026)
The Nieuwe Waterweg is the artificial mouth of the Rhine and Meuse Rivers in the Netherlands and an important shipping channel for the Port of Rotterdam. The channel, about a half-kilometer wide, is dredged to depths of more than 16 m to allow navigation. This substantial depth has adverse effects on flood safety, ecology and salinity intrusion in the lower river system. Mitigating these effects through engineering is costly and increasingly unviable with rising sea levels. A straightforward, nature-based alternative is to allow natural sedimentation, gradually making the channel shallower again while the port continues to expand seaward. We present 1:1000 scale physical experiments as a future vision for sedimentation in the ports and the Nieuwe Waterweg. The observed behavior aligns with that of similar estuaries and ports worldwide, demonstrating the broader applicability of this approach. Based on the current sediment budget, the sedimentation rate is estimated 0.5–1.0 m per decade. If transitional and structural changes in port logistics are coordinated with this sedimentation rate, the port economy can be expected to benefit.
Keywords: Sea level rise; Dredging; Port; Salinity intrusion; Analogue scale modeling